2014
DOI: 10.5811/westjem.2013.11.19232
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Abbreviated Cardiac Enzyme Protocol to Aid Rapid Discharge of Patients with Cocaine-associated Chest Pain in the Clinical Decision Unit

Abstract: IntroductionIn 2007 there were 64,000 visits to the emergency department (ED) for possible myocardial infarction (MI) related to cocaine use. Prior studies have demonstrated that low- to intermediate-risk patients with cocaine-associated chest pain can be safely discharged after 9–12 hours of observation. The goal of this study was to determine the safety of an 8-hour protocol for ruling out MI in patients who presented with cocaine-associated chest pain.MethodsWe conducted a retrospective review of patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“… [13] Lastly, a more recent study by Guirgis et al (2014) advised an eight-hour discharge protocol which consists of serial cardiac biomarker testing, including troponin T, at 0, 2, 4 and 8 hours after presentation. [14] In this study, which involved 101 patients, neither ACS nor fatalities were reported within the subsequent 30-day follow-up duration. [14] These last three studies show that none of the observed patients developed ACS, which is concordant with the results of this study, suggesting that a prolonged observation period is not necessary for CACP patients.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“… [13] Lastly, a more recent study by Guirgis et al (2014) advised an eight-hour discharge protocol which consists of serial cardiac biomarker testing, including troponin T, at 0, 2, 4 and 8 hours after presentation. [14] In this study, which involved 101 patients, neither ACS nor fatalities were reported within the subsequent 30-day follow-up duration. [14] These last three studies show that none of the observed patients developed ACS, which is concordant with the results of this study, suggesting that a prolonged observation period is not necessary for CACP patients.…”
Section: Discussionmentioning
confidence: 76%
“… [14] In this study, which involved 101 patients, neither ACS nor fatalities were reported within the subsequent 30-day follow-up duration. [14] These last three studies show that none of the observed patients developed ACS, which is concordant with the results of this study, suggesting that a prolonged observation period is not necessary for CACP patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…CACP is characterized by symptoms similar to those of acute coronary syndrome, including constrictive or oppressive retrosternal pain (11,13,15). However, <6% of patients with transient CACP have myocardial infarction or an underlying coronary lesion (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Because the proportion of enzymes in drug target proteins is higher, recognizing enzymes is more and more essential for the research of drug targets. [5][6][7][8][9][10][11] Faced with the urgent need of information about enzymes, the following questions have been raised: can we get the appropriate information on enzymes? If we can, is it enough, abundant and reliable?…”
Section: Introductionmentioning
confidence: 99%